Sustainable Supply Chain Strategies to Enhance the Global Competitiveness of Clove Commodities in North Sulawesi - Palandeng, Indrie Debbie; Tielung, Maria V. J.; Wangke , Shinta Jeanette C.; Tumiwa, Johan Reineer; Tumewu, Ferdinand J. (Sam Ratulangi University, 2026)
This study develops an integrated sustainable supply chain strategy to strengthen the global competitiveness of clove commodities in North Sulawesi. The research employs a qualitative descriptive approach, involving farmers, collectors, exporters, and government institutions, to examine supply chain conditions, identify internal and external strategic factors, and formulate actions to improve long-term competitiveness. Using SWOT, IFAS–EFAS, and TOWS analysis, the study reveals that intrinsic product quality, traditional knowledge, and strong social networks form the core strengths of the upstream actors, while major weaknesses include aging trees, inconsistent post-harvest quality, limited logistics infrastructure, and restricted market access. Externally, the clove sector has strong opportunities in premium global markets, digital supply chain transformation, certification potential, and product diversification; yet it faces significant threats, including international competition, price volatility, climate risks, and non-tariff trade barriers. The formulated strategies emphasize modernization of cultivation and post-harvest practices, digital traceability systems, structured replanting programs, cooperative-based distribution models, certification clusters, and the development of value-added derivative products. The study contributes a strategic roadmap that integrates sustainability, digitalization, and institutional collaboration to enhance supply chain efficiency, stabilize farmer welfare, and elevate the global market position of North Sulawesi cloves. Keywords: Clove supply chain; sustainable supply chain; competitiveness; TOWS strategy; IFAS–EFAS; agricultural value chain; digital traceability.